Are Kenyans Likely to Use COVID-19 Self-Testing Kits? Results From a Cross-Sectional Survey - Griffins Manguro; Sonjelle Shilton; Sharon Omenda; Patrica Owira; Deepshikha Batheja; Abhik Banerji; Sophie Vusha Chabeda; Marleen Temmerman; Marleen Temmerman; Walter Jako; Joseph Ndungu; Stanley Luchters; et al. (Frontiers Media S.A., 2022)
Objectives: To understand the public's perceptions around rapid SARS-CoV-2 antigen self-testing in Kenya, including the drivers of acceptability, willingness to pay, and adherence to hygiene and prevention recommendations following a positive self-test.Methods: A household-based, cross-sectional survey, using a 35-item questionnaire, was conducted in Mombasa and Taita-Taveta counties, Kenya, during August 2021. Individuals aged ≥18 years were enrolled using a stratified sampling approach.Results: There were 419 participants (mean age 35.7 years). A minority (10.5%) had ever tested for SARS-CoV-2. If SARS-CoV-2 self-testing were available, 39.9% and 41.5% would be likely and very likely, respectively, to use it. If unavailable free-of-charge, 63.01% would pay for it. Multivariate analyses suggested that people in rural areas (Coefficient 0.30, 95%CI: 0.11-0.48, p = 0.002), aged 36-55 (Coefficient 0.21, 95%CI: 0.03-0.40, p = 0.023), and employed full time (Coefficient 0.32, 95%CI: 0.06-0.58, p = 0.016) would have more odds to adhere to recommended hygiene and prevention actions.Conclusion: SARS-CoV-2 self-testing was considered acceptable. Availability of self-testing could expand access to COVID-19 testing in Kenya, particularly among rural communities who have limited access to testing, and among mildly symptomatic individuals.